2018
DOI: 10.1098/rsos.171578
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the route for production of activated carbon fromCasuarina equisetifoliafruit waste

Abstract: This work deals with optimizing the conditions of pyrolysis and type of activator to upgrade the use of Casuarina equisetifolia fruit waste (CFW) as available and a potential precursor, in production of activated carbon (AC). In this respect, the route of activation was carried out through one- and two-step pyrolysis processes, using different chemical activating agents, such as H3PO4, KOH and ZnCl2. The performance of the CFW-based ACs is assessed by estimating the physico-chemical characteristics (pH, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 46 publications
(66 reference statements)
0
17
0
2
Order By: Relevance
“…A large number of pores can be observed, caused by the chemical interaction between the precursor surface and the activation agent (KOH). The obtained pores were irregular and oval, like embedded deep holes typically observed after chemical activation (El-Naggar et al, 2015 ; Ravichandran et al, 2018 ). BAG images denote areas with material agglomerates, where porosity is found between these mass portions.…”
Section: Resultsmentioning
confidence: 77%
“…A large number of pores can be observed, caused by the chemical interaction between the precursor surface and the activation agent (KOH). The obtained pores were irregular and oval, like embedded deep holes typically observed after chemical activation (El-Naggar et al, 2015 ; Ravichandran et al, 2018 ). BAG images denote areas with material agglomerates, where porosity is found between these mass portions.…”
Section: Resultsmentioning
confidence: 77%
“…Heidari et al prepared ACs with high surface area (2595 m 2 g −1 ) using H 3 PO 4 as a first activating agent followed by KOH as a second activating agent (Heidari et al 2014). It was mentioned that a two-step activation method produces up to 25% higher carbon yields activated carbon than that of a single-step activation method along with 50% higher surface area and pore volume also (Ravichandran et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The XRD analysis gives an indication of the crystalline structures present in the sample, thus allowing identification of components such as cellulose; one of the main constituents of biomass samples. Cellulose crystallinity can be in the form of amorphous (diffraction lines at 2θ = 18°) or crystalline (diffraction lines at 2θ = 22° corresponding to the crystallographic plane (002) with JCPDS data 03–0289), whereas both hemicellulose and lignin are known to be amorphous in nature …”
Section: Resultsmentioning
confidence: 99%
“…The use of an activating agent does not have to be restricted to one step; once a char has been mixed with an activating agent and pyrolyzed, it can be activated further using a second activating agent. Ravichandran et al reported that a two‐step activation of the biomass could produce a higher adsorption AC with greater performance than a single activation AC. Compared to a one‐step activation, the two‐step activation was found to produce AC with ≤25% higher carbon yields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation